A quantitative approximation on spirituality in hospitalized older adults, a nursing care opportunity - Castañeda Flores, Teresa; Guerrero Castañeda, Raúl Fernando (Revista Cuidarte, 2019)
Introduction: Spirituality and religiosity influence longevity, coping with death, and life satisfaction, apart from providing illness support. This study aims to describe the spiritual perspective of older adults hospitalized in a secondary level healthcare institution. Materials and Methods: A quantitative, observational and cross-sectional study was conducted in internal medicine and surgery departments at the Rincón de Romos Hospital, Aguascalientes, using a non-probability sampling for convenience. The inclusion criteria were: older adults with at least 24 hours of hospitalization, men and women over 60 years of age. The Reed’s Spiritual Perspective Scale was used, the higher the score the higher the spirituality, including a section on sociodemographic characteristics. Additionally, a descriptive analysis through frequencies and percentages was made. Results: The average age of participants was 69.7 years (Min 62, Max 94, DE 7.31). 80.4% of the participants considered that they did not receive any spiritual or religious support from nurses during their hospital stay, 29.4% talked about spiritual matters at least once a week and 70.6% agreed that forgiveness is an important part of spirituality. Discussion: Spiritual care should be part of nurses’ daily life since older adults focus on prayer and spiritual reading, considering spirituality as an important element in their life. Conclusions: There is a high spiritual sense in older adults, which can support their emotional state during hospitalization, becoming an important factor to consider when caring hospitalized older adults.How to cite this article: Castañeda-Flores T, Guerrero-Castañeda RF. Espiritualidad en adultos mayores hospitalizados: Aproximación cuantitativa. Rev Cuid. 2019; 10(3): e724. http://dx.doi.org/10.15649/cuidarte.v10i3.724
Keywords: Aged; Spirituality; Nursing